Promoting Personal Learning Environment for Emerging Academic Writing for Publication for Higher Education Students - Nur Arifah Drajati; A'thi Fauzani Wisudawati; Anis Handayani (UIN Salatiga, 2020)
Academic writing for publication in higher education is cognitively and linguistically complex. University students grapple with academic writing for publication because of academic genre/convention, linguistic competence, and academic literacy among others. For this reason, a learning environment does matter. The Personal Learning Environment (PLE) is a learner-controlled environment for language learning. To examine this issue, a qualitative study with an action research design conducted with 28 graduate students as participants. The three main findings: (1) ways of encouraging students to write academic writing for publication through the personal learning environment as a learning platform; (2) implementing PLE's in the academic writing for publication course: content knowledge consideration; and (3) implementing PLE's in the academic writing for publication course: pedagogical consideration. In general, the findings indicate that PLE gives positive impacts on emerging students' academic writing for publication in the context of higher education. The educational organization needs to consider this issue. Keywords: Action research, academic writing for publication, learning autonomy, personal learning environment